1995
DOI: 10.1016/s0741-5214(95)70135-4
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Greenfield filter placement in selected high-risk trauma patients

Abstract: PGF insertion in selected patients at high risk who had trauma effectively prevented both fatal and nonfatal PE. The lower incidence of fatal PE in the PGF group may have contributed to a reduction in the overall mortality rate. Patients who have trauma with high risk for PE should be considered for PGF placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(104 citation statements)
references
References 21 publications
(2 reference statements)
2
100
0
2
Order By: Relevance
“…Fifty-eight studies addressed IVC filter use in trauma, although most (n = 48) were uncontrolled studies. We included 8 controlled studies that assessed the effectiveness of IVC filter compared with no filter placement on VTE events in trauma patients ( ; 4, prospective cohort studies with historical controls 27,[29][30][31] ; and 1, a retrospective cohort study.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifty-eight studies addressed IVC filter use in trauma, although most (n = 48) were uncontrolled studies. We included 8 controlled studies that assessed the effectiveness of IVC filter compared with no filter placement on VTE events in trauma patients ( ; 4, prospective cohort studies with historical controls 27,[29][30][31] ; and 1, a retrospective cohort study.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…25,27,28,[30][31][32] We In the small RCT, 25 we found no statistically significant difference in the incidence of PE between the 2 groups, with no PEs in the IVC filter group and 1 PE among patients without filters. Five of the 6 observational studies included in the metaanalysis reported lower PE rates with IVC filter placement [27][28][29][30][31] ( …”
Section: Outcomes Pulmonary Embolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The IVC wall was penetrated in 9%, and PE with a filter in place developed in up to 10%; 6% of permanent IVC filters migrated and filter fractures were observed in 2% (Table 1). In view of these data, the indiscriminant prophylactic use of permanent IVC filters should be avoided [2,[4][5][6][7][8].…”
Section: Materials: Permanent and Temporary Filtersmentioning
confidence: 99%
“…Inferior VCFs are effective in preventing PE [17][18][19], but they do not prevent DVT or postthrombotic syndrome. In high-risk trauma patients without DVT, prophylactic insertion of a VCF has shown to decrease the rate of PE in multiple studies [20][21][22]. Interruption of the inferior vena cava (IVC) for the prevention of PE has become popular in trauma patients.…”
Section: Introductionmentioning
confidence: 99%